2020
DOI: 10.1101/2020.08.07.240580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory signatures of drought response in stress resilientSorghum bicolor

Abstract: The effects of drought stress can be devastating to crop production worldwide. A grand challenge facing agriculture is the development of crop varieties with improved drought resilience through breeding or biotechnology. To accelerate this, a mechanistic understanding is needed of the regulatory networks underlying drought response pathways in crop genomes and the genetic elements that modulate them. In this study, we explore the regulatory landscape of sorghum [Sorghum bicolor (L.) Moench] in response to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…In maize, however, the use of chromatin accessibility data derived from plants grown in control conditions does not improve predictions of heat or cold stress responses (158). In sorghum, drought-responsive accessible chromatin signatures were enriched for ABSCISIC ACID RESPONSE ELEMENT (ABRE)-binding sites and used to constrain gene regulatory network predictions for abscisic acid-dependent transcriptional cascades (106). Further analyses using dynamic chromatin accessibility in both control and stress samples may provide insights into whether chromatin data can improve stress-response predictions.…”
Section: Environmental Responsesmentioning
confidence: 99%
“…In maize, however, the use of chromatin accessibility data derived from plants grown in control conditions does not improve predictions of heat or cold stress responses (158). In sorghum, drought-responsive accessible chromatin signatures were enriched for ABSCISIC ACID RESPONSE ELEMENT (ABRE)-binding sites and used to constrain gene regulatory network predictions for abscisic acid-dependent transcriptional cascades (106). Further analyses using dynamic chromatin accessibility in both control and stress samples may provide insights into whether chromatin data can improve stress-response predictions.…”
Section: Environmental Responsesmentioning
confidence: 99%
“…Recent work has suggested that unmethylated regions may provide a catalogue of potential regulatory elements in plants (Crisp et al, 2020). Many regions that contain stress-specific regulatory elements are likely unmethylated even in control conditions while many of the regions of accessible chromatin may be more dynamic and only become accessible in specific conditions (Zeng et al, 2019; Wang et al, 2020a; Parvathaneni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei isolation was carried out using a modified version of Parvathaneni et al., 2021’s protocol ( Parvathaneni et al., 2021 ). Fifteen developing kernels were finely chopped with razor blades in a nuclei isolation buffer (16 mM HEPES; pH8, 200 mM sucrose, 0.8 mM MgCl2, 4 mM KCl, 32% Glycerol, 0.25% Triton X-100, 1x complete protease inhibitor, 0.1% 2-ME, 0.1 mM PMSF).…”
Section: Methodsmentioning
confidence: 99%